If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5g + -20 + 12 = 1 + -1g Reorder the terms: -20 + 12 + 5g = 1 + -1g Combine like terms: -20 + 12 = -8 -8 + 5g = 1 + -1g Solving -8 + 5g = 1 + -1g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add 'g' to each side of the equation. -8 + 5g + g = 1 + -1g + g Combine like terms: 5g + g = 6g -8 + 6g = 1 + -1g + g Combine like terms: -1g + g = 0 -8 + 6g = 1 + 0 -8 + 6g = 1 Add '8' to each side of the equation. -8 + 8 + 6g = 1 + 8 Combine like terms: -8 + 8 = 0 0 + 6g = 1 + 8 6g = 1 + 8 Combine like terms: 1 + 8 = 9 6g = 9 Divide each side by '6'. g = 1.5 Simplifying g = 1.5
| 2x+7=3x-17 | | 3x^2-430x-11000= | | 18-5(2x+4y)= | | 3=39/y | | -11+3(b+5)=7 | | X-x-15=0 | | -1/9(x+27)+1/3(x+3)=x+25 | | sex=sex | | 2w+17=18 | | 5x-4(2x+11)=14 | | 7*-4=c | | 6-3y+12=0 | | 18-5(2x+47)= | | 49x^2+70x+25=x | | 4n+6=2(n+3) | | -1/2(4m+8) | | t/2+6=10 | | -6.2=1.3m | | -6n+4=-14 | | -3/2(12x-8)=-18 | | x-8=-4x-8 | | 3u-3=4u-2 | | 3x+6=11+-2x-1 | | 5x+2=-2+3x+10 | | 1/2+6=10 | | 2x-17=x+55 | | 21c+7-4c=39c-26 | | 8y^2-4y+14=0 | | 42m^5n+28m^4=0 | | 8x-(5x+11)=16 | | 3x+6=11x+-2x | | 11/10= |